Financial Reporting of Antitrust Actions . - Schattke, R. W. (The Accounting Review, 1965)
Abstract The article examines the way in which antitrust matters are handled in financial reporting. The reports of two major companies, General Electric Co. and Westinghouse Corp., are chosen. Examination is limited to the published annual reports of the companies. Since disclosures were similar up until the time that losses were actually recorded, both companies are treated together in 1939, 1960, and 1961. After that, reporting diverged so both companies are dealt with separately in 1962, 1963, and 1964. In 1960 both companies had already pleaded guilty on the various actions in the antitrust suits. The record of their approach to the problem should lead one to certain conclusions as to the adequacy of their response to this reporting challenge. The differences in treatment are considerable and indicate clearly the possible diversity in present accounting practice. The way in which the reporting challenge was met by these two companies indicates a wide diversity in accounting practice and suggests a lack of imagination in dealing with a problem that involves some complex questions of disclosure and reporting.